Book Reviews (The ecumenical review, 1954)
Book reviewed in this article: JESUS CHRIST — THE GROUND AND OBJECT OF OUR HOPE: Christian Hope and the Second Coming, by Paul S. Minear. NINETEEN CENTURIES OF THE GREEK CHURCH: Saint Paul's Mission to Greece. NINETEEN CENTURIES OF THE GREEK CHURCH: Ta dogmatika kai symbolika mnemeia tes orthodoxou katholikes ekklesias (The Dogmatic and Symbolic Statements of the Orthodox Catholic Church), by Ioannes Karmiris. ISRAEL — OLD AND NEW: The Church and the Jewish People, a symposium, edited by Göte Hedenquist. WRESTLING WITH COMMUNISM: Christian Faith and Communist Faith, edited by D. M. Mackinnon. A series of studies by members of the Anglican Communion. WRESTLING WITH COMMUNISM: Marxism: An interpretation, by Alasdair McIntyre. WRESTLING WITH COMMUNISM: Marxismusstudien. Beiträge von H. Bollnow, F. Delekat, I. Fetscher, L. Landgrebe, R. Nürnberger, H. H. Schrey, E. Thier, H. D. Wendland. Vorwort von Erwin Metzke. (Schriften der Studiengemein-shaft der Evangelischen Akademien.) WRESTLING WITH COMMUNISM: Communism and the Social Revolution in India: A Christian Interpretation, edited by P. D. Devanandan and M. M. Thomas WRESTLING WITH COMMUNISM: Marxismus und Christentum, by Emil Fuchs. WRESTLING WITH COMMUNISM: The Challenge of Communism; The Churches Under Communism. Reports of the General Assembly of the Church of Scotland. WRESTLING WITH COMMUNISM: The Churches of Europe Under Communist Governments: A Survey written by a member of the Church of England's Council of Foreign Relations at the Council's Request.